2015
DOI: 10.1109/jqe.2015.2442760
|View full text |Cite
|
Sign up to set email alerts
|

Study of Wavelength Dependence of Mode Instability Based on a Semi-Analytical Model

Abstract: We present theoretical study of wavelength dependence of mode instability (MI) in high power fiber lasers, which employs an improved semi-analytical theoretical model. The influence of pump/seed wavelength and photodarkening on threshold has been studied. The results indicate promising MI suppression through pumping or seeding at an appropriate wavelength. Small amounts of photodarkening can lead to a significant impact on MI.Index Terms-Mode instabilities, fiber amplifier, thermal effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Previously, our research group used the semi-analytical model to calculate the TMI threshold under different signal wavelengths in the high power YDF amplifier [16,32], the highest TMI threshold can be obtained by operating at a seed wavelength of around 1032 nm. By shifting the seed signal to longer or shorter wavelengths, the TMI threshold drops and the decrease in the longer wavelength is steeper than that in the shorter wavelength, which is also observed in [27].…”
Section: Tmi Threshold Comparison and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our research group used the semi-analytical model to calculate the TMI threshold under different signal wavelengths in the high power YDF amplifier [16,32], the highest TMI threshold can be obtained by operating at a seed wavelength of around 1032 nm. By shifting the seed signal to longer or shorter wavelengths, the TMI threshold drops and the decrease in the longer wavelength is steeper than that in the shorter wavelength, which is also observed in [27].…”
Section: Tmi Threshold Comparison and Discussionmentioning
confidence: 99%
“…However, power scaling of the monolithic fiber laser systems with near-diffraction-limited beam quality to multi-kilowatt level has been challenged by the limitations of nonlinear effects, fiber damage and transverse mode instability (TMI) [10][11][12]. Among the limitations, TMI refers to a sudden onset of beam fluctuations together with significant degradation of beam quality, when the output average power exceeds a certain threshold [1], which is one of the major limiting factors for the further power scalability of continuous wave fiber lasers [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the ytterbium ion has the largest absorption cross-section at 976 nm. The larger absorption cross-section will lead to higher upper states populations and a decrease of spatial hole burning [11,22]. Beyond that, the larger absorption cross-section will cause a lot of heat to collect in the first few meters of the active fiber [27].…”
Section: B Performance Of the Fiber Laser Amplifier Pumped By Nonwavelength-stabilized 976 Nm Ldmentioning
confidence: 99%
“…Because of its far-reaching influence, after the first report of the TMI phenomenon, the researchers put forward lots of effective methods to mitigating the TMI effect [11][12]. Such as designing the structure of active fiber [13][14][15][16], optimizing the structure of the fiber laser [17][18][19][20], shifting the pump and signal wavelength and pump power distribution [21][22][23], and so on. Among these suppression methods, optimizing the pumping wavelength to increase the TMI threshold is easy to realized and proved very effective.…”
Section: Introductionmentioning
confidence: 99%
“…Although TMI does not directly restrict the power scaling, it will cause a sharp deterioration in beam quality and affect the stability of the laser system [6][7][8][9][10]. So far, much evidence has indicated that TMI may originate from STRS [11][12][13][14], according to which researchers have established various TMI static models based on STRS [12,[15][16][17][18]. These models analyze the nonlinear coupling process between the fundamental mode and the higher-order modes to investigate the TMI characteristics under the assumption that the phase shift between the mode interference pattern and the refractive index grating is usually π/2.…”
Section: Introductionmentioning
confidence: 99%